Technical Appliance in E-Learning: Student’s Perception on the Usage of Online Learning - Mohd Johari, Siti Sarah; Ismail, Issham; Mohammed Idrus, Rozhan (International Journal of Emerging Technologies in Learning (iJET), 2010)
The purpose of this study is to gain insights into studentâ??s perception on the usage of technical appliances on online learning. The study took place in the Universiti Sains Malaysia (USM) based on the sample of 1084 student s with the experiences of using E-learning Portal as one of the distance education academic programme. The students were surveyed on the participation needs based on respondentâ??s personal background, such as age, gender, ethnic groups, education streams and year-of-study. Results of the study showed even though most of the students felt uncertain about the technical appliances in E-learning Portal, the study illustrates the true nature of the studentâ??s perceptions with respect to the functionality and effectiveness of technical appliance in E-learning Portal. This research is essential to elucidate the functions of technical appliances in facilitating the process of learning through the portal.